PERKEMBANGAN FISIK ANAK, PROBLEM DAN PENANGANANNYA - Wiwit Eka Winarsih (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2021)
Man sano in carpore sano (in a healthy body there is a healthy soul), physical developmentis usually marked by changes in height and weight, as well as body shape and braind development If the child's physical development develops well, it will certainly affect their motors skills Likewise with children whose physical development is impaired, it will have an impact ont thedisruption of the child's motor skills. Therefore, this paper will discuss three important issues,first how the understanding and characteristics of children's physical development, second, whata are the stages of children's physical development and third, what are the problems of children's physical development and how to deal with them. This paper is in the form of a literature review by digging from various sources of books and journals, in order to obtain a comprehensive understanding of the meaning and characteristics of children's physical development, stages of children's physical development, problems and handling of children's physical development